2011
DOI: 10.4049/jimmunol.1002825
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II-Restricted Interaction between Thymocytes Plays an Essential Role in the Production of Innate CD8+ T Cells

Abstract: We have recently shown that MHC class II-dependent thymocyte–thymocyte (T-T) interaction successfully generates CD4+ T cells (T-T CD4+ T cells), and that T-T CD4+ T cells expressing promyelocytic leukemia zinc finger protein (PLZF) show an innate property both in mice and humans. In this article, we report that the thymic T-T interaction is essential for the conversion of CD8+ T cells into innate phenotype in the physiological condition. CD8+ T cells developed in the presence of PLZF+ CD4+ T cells showed marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
97
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 30 publications
10
97
1
1
Order By: Relevance
“…It has been proposed that they could act as early sensors of an inflammatory environment during primary infection. Recently, Eomes expressing memory-like cells rapidly secreting IFN-g upon TCR triggering have been described in the fetal spleen and thymus at 18 wk of gestation (44). These cells could play an important role in the newborn immune response, before the maturation of their immune system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that they could act as early sensors of an inflammatory environment during primary infection. Recently, Eomes expressing memory-like cells rapidly secreting IFN-g upon TCR triggering have been described in the fetal spleen and thymus at 18 wk of gestation (44). These cells could play an important role in the newborn immune response, before the maturation of their immune system.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, different subsets of innate T cells with diverse TCR repertoire have been reported (11,12). Promyelocytic leukemia zinc finger protein + (PLZF + ) CD4 T cells generated by MHC class II-dependent thymocyte-thymocyte (T-T) interaction (T-T CD4 T, also referred to as T-CD4 T) are included in this group (11).…”
mentioning
confidence: 99%
“…Subsequent experiments revealed that some proportion of the T-T CD4 T cells in CIITA tg pIV 2/2 mice expressed PLZF, which was identified as a transcription factor necessary for the development of invariant NKT (iNKT) cells and for directing the innate characteristics of iNKT cells (17). Very recently, we reported on another subset of CD8 T cells that were developed in the presence of IL-4 produced by PLZF + T-T CD4 T cells, and showed upregulated expression of eomesodermin (Eomes) in CIITA tg pIV 2/2 mice (12). Both PLZF + T-T CD4 T cells and Eomes + CD8 T cells have innate characteristics and diverse TCR repertoires (18); they are also found in humans (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…également aux réponses immunitaires en début et en fin de vie, deux périodes de susceptibilité accrue aux infections. L'existence de ces cellules non conventionnelles chez l'homme n'est pas encore formellement démontrée, mais plusieurs études ont mis en évidence une population de lymphocytes T CD8 + de phéno-type mémoire dans les rates et le sang de cordon de foetus humains [10]. …”
Section: Par Quels Mécanismes Un Lymphocyte T Cd8 + Naïf Acquiert-il unclassified